Process observations from an Australian cooperative inquiry project aimed at improving undergraduate student's experience. (November 2015) - Howard, A; Agllias, K; Cliff, K; Dodds, J; Field, A
This paper reports on a collaborative student-for-student research project conducted in 2012, which aimed to improve the first year experience for students at one Australian University. A cooperative inquiry group was established to focus on the issues experienced by first year students from low socio-economic backgrounds, raise critical consciousness, question existing ideological constructs and develop a response to the identified issues in the form of a V-pod. Thematic analysis of recorded data from meetings and written data from group wiki pages revealed three key themes related to: sharing experience, sharing power and sharing time. Findings suggest a clear place for cooperative inquiry in the higher educational sector, but this must be supported by the time and space to establish collaborative relationships. When academics and students recast their roles as 'the researcher' and 'the researched' in the pursuit of co-created knowledge they are more able to rally against structural barriers and produce more meaningful outcomes.